(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
Preschool age is a period of active mastery of the child’s spoken language, the formation and development of all aspects of speech - phonetic, lexical, grammatical. Full knowledge of the native language of preschool age is a necessary condition for solving the problems of mental, aesthetic and moral upbringing of children in the most delicate period of development. Children with specific needs have been recognized. have many of the same traits as youngsters who are usually developing. These children may take longer to develop their speech, while others may have deficits that are not diagnosed at birth but become more obvious with time, and still others may struggle in school, with issues ranging from concentration, learning, language, and perception to behavioral issues. This page explains terms and topics related to normal speech and language development, communication, language disorders, and language differences. It also outlines how professionals can interact with primary caregivers to provide necessary services for students in school programs who are facing language problems.